PRE-LISTENING ACTIVITIES AND THEIR INFLUENCE ON EFL LEARNERS' LISTENING COMPREHENSION (A QUASI EXPERIMENTAL RESEARCH AT THE ENGLISH STUDY PROGRAM STUDENTS) - Putri, Nurida Andela; Hakim, M. Arif Rahman; Revola, Yashori (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the Effect of pre-listening activities on the listening ability of UINFAS Bengkulu 4th semester English students. The method used in this research is a quantitative method using a quasi-experimental design. The sample in this study was 40 students consisting of 20 students in the experimental class (4 B) and 20 students in the control class (4 D) who were taken using purposive sampling. The experimental class is the class that is treated using the pre-listening activities strategy, while the control class is the class that does not use the pre-listening activities strategy. Pre-test was given in two groups before giving treatment. The research results showed that the average pre-test score for the experimental class was 51.00 and the control class was 50.75. After being given treatment, a post-test was given. The post-test results show that the average score for the experimental class is 73.75 and the control class is 62.75. Furthermore, the sample score from the independent T-test shows that the significant value (2 tailed) is 0.000 <0.05. In other words, Ho is rejected and Ha is accepted. In short, it can be said that students who are taught using the pre-listening activities strategy are more effective. It can be concluded that learning using the pre-listening activities strategy has a positive influence on 4th semester English students at UINFAS Bengkulu.